SHIFTING CULTIVATION SYSTEM A HUMAN ECOLOGICAL ADAPTATION TOWARDS TROPICAL RAIN FOREST ENVIRONMENT - Harihanto Harihanto (Bumi Lestari Journal of Environment, 2010)
Shifting cultivation is the oldest agricultural system widely practiced until now especially in tropical areas. Since this system requires relatively extensive use of land and uses slush and burn technique it is often labeled as a main cause of deforestation and land degradation. Each household of farmers needs about 1 – 5 hectares of land for shifting cultivation. On the other hand a lot of researchers have different opinions. They believed that shifting cultivation system has positive influenced on environment because it can increase biological diversity. Many studies show that the system does not caused permanent land degradation as long as the fallow period is not too short. Many scientists believe that if the system causes environment degradation then a lot of forested areas in Indonesia will have turned into desert now. Shifting cultivation practiced by Dayak communities in Kalimantan does not cause serious deforestation.